Dissecting the deep biosphere: retrieving authentic microbial communities from packer‐isolated deep crystalline bedrock fracture zones. Issue 2 (2nd May 2013) - Purkamo, Lotta; Bomberg, Malin; Nyyssönen, Mari; Kukkonen, Ilmo; Ahonen, Lasse; Kietäväinen, Riikka; Itävaara, Merja
Abstract: Deep fracture zones in Finnish crystalline bedrock have been isolated for long, the oldest fluids being tens of millions of years old. To accurately measure the native microbial diversity in fracture‐zone fluids, water samples were obtained by isolating the borehole fraction spanning a deep subsurface aquifer fracture zone with inflatable packers (500 and 967 m) or by pumping fluids directly from the fracture zone. Sampling frequency was examined to establish the time required for the space between packers to be flushed and replaced by indigenous fracture fluids. Chemical parameters of the fluid were monitored continuously, and samples were taken at three points during the flushing process. Microbial communities were characterized by comparison of 16S ribosomal genes and transcripts and quantification of dsr B (dissimilatory sulfate reduction) gene. Results suggest that fracture‐zones host microbial communities with fewer cells and lower diversity than those in the drill hole prior to flushing. In addition, each fracture zone showed a community composition distinct from that inhabiting the drill hole at corresponding depth. The highest diversity was detected from the 967‐m fracture zone. We conclude that the applied packer method can successfully isolate and sample authentic microbial fracture‐zone communities of deep bedrock environments.